Exchange rate volatility, external shock, and capital inflows in Nigeria - Ahmed, Sani Idris (2016)
This research focuses on exchange rate volatility, external shock, and capital inflows. The study uses secondary data for the period of 1986 to 2014 for its analysis. The three specific objectives of the study are to investigate whether current exchange rate volatility has any relationship with its conditional volatility in periods ahead using Exponential Generalized Autoregressive Conditional Heteroskedasticity (EGARCH) technique; to examine the impact of external shocks on exchange rate volatility; and to evaluate the relationship between capital inflows and exchange rate volatility using Autoregressive Distributed Lags (ARDL) and Johansen co-integration methods, respectively. The results show that current exchange rate volatility is related to its conditional volatility in periods ahead, external shock significantly impacted on exchange rate volatility and that exchange rate volatility significantly explains capital inflows. Based on these findings, the research recommends that minimizing effects of exchange rate volatility on its conditional volatility in periods ahead. So, the government needs proactive monetary and fiscal policies like prudent allocation of foreign currencies through Central Bank of Nigeria, direct swap of Naira to other currency aside United States Dollar (USD), and diversifying the economy to increase non-oil exports. The study suggested that political instability can be addressed through jobs creation for the youth like investment in small and medium enterprises, provision of affordable basic necessities of life, proper remuneration and equipping the security agencies. On oil price, the government should diversify the economy for the solid minerals and agricultural sectors to lead as Nigeria exports. The recommendations on financial crisis are that government should have a database for prompt response and forecasting. Financial leakage should address and reckless corrupt practices should legally deal with. This study equally recommends conducive legal, stable infrastructure, and reliable security framework for achieving sustainable capital inflows.